Destination Middle East : a handbook for Filipino women domestic workers - Alunan, Gina M. (Kanlungan Centre Foundation, Inc., 1997)
Aims to provide ready-reference information regarding general issues and concerns of Filipino women domestic helpers. With statistics and simple black and white illustrations. Written in an easy-to-read style and is intented for the use of the general public.